Peran Iklim Sekolah, Dukungan Otonomi dan Harga Diri terhadap Kepuasan Bersekolah Siswa - Wilantika, Rima; Rustam, Husnul Khotimah; Hidayah, Nurul; Purwadi, Purwadi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2022)
The routine of students is to go to school and get their education at school. Of course, students have faced academic, non-academic tasks, friendships, teacher staff and other school equipment that trigger students' school satisfaction. The purpose of this study was to determine the role of parental support for autonomy, self-esteem and school climate on school satisfaction in high school students. This goal is strengthened by the technique of multiple linear regression analysis. To test this objective, the researcher tested 82 students of SMAN 1 Ambarawa, Pringsewu, Lampung Regency. The instrument used is four scales, namely the scale of parental autonomy support, self-esteem scale, school climate scale and school satisfaction scale. The finding of this study is that there is a positive correlation between parental support for autonomy, self-esteem, and school climate on school satisfaction for high school students. The data has a significance level of 0.001. Implicitly, this study finds school satisfaction is influenced by parental support for autonomy and a positive school climate. Individuals are able to feel satisfaction with the school which is an indication of a healthy school. Parental support that allows children to choose every decision and knows the risks taken is able to maintain children's school satisfaction. Children become comfortable with their environment. The implication of this research is that this school familiarizes the behavior and attitudes of students with polite and good words so that there is no bullying or aggressiveness that supports the satisfaction of students, teachers and principals.